Geospatial analysis of limited access to drinking water services in East African countries: insights from recent demographic and health surveys - Yitageasu, Gelila; Chekole Adane, Kassaw; Tesfaye, Amensisa Hailu; Gizaw, Zemichael; Kifle, Tigist; Demoze, Lidetu (Frontiers in Water, 2025)
BackgroundLimited access to water caused by its scarcity is becoming one of the most serious problems facing several developing countries including East Africa. For this, understanding the spatial distribution of limited access to water source service is more pertinent. The purpose of this study is to analyze the spatial distribution of limited access to water source services in East Africa countries and seeks to inform the development and implementation of targeted interventions and policies in East Africa.MethodsThis study analyzed data from recent demographic and health surveys conducted in 12 East African nations between 2012 and 2023. Data were gathered from 206,748 households. Global spatial autocorrelation was performed to analyze whether the pattern of limited access to drinking water service is clustered, dispersed, or random across the study areas. Once a positive global autocorrelation was confirmed, a local spatial autocorrelation analysis (Getis-OrdGi* statistics) was employed to detect local clusters. ArcGIS Pro 2.8.0 was used to map the clusters and Kulldorff SaTScan version 10.0.2 software using Bernoulli model were used for spatial scan statistical tests. The geostatistical ordinary kriging spatial interpolation technique was used to predict for unsampled areas based on sampled clusters.ResultLimited access to drinking water service were spatially clustered in the study area (Moran’s I: 0.16) (p < 0.0000). 40 significant clusters of which, one primary cluster and 39 secondary clusters were identified. The first spatial window which contains primary clusters was located in Uganda and Rwanda. The other 39 secondary spatial clusters were observed in Malawi, Mozambique, Kenya, Ethiopia and small part of Madagascar. Cold spot clusters were identified Madagascar, Zimbabwe, Tanzania, Comoros, Zambia and some parts of Kenya.ConclusionThe result of this study revealed the existence of spatial variation of limited access to drinking water services in East Africa. The variation was observed both within and across the countries. Engaging practitioners, researchers, policymakers, and local communities through multi-stakeholder platforms will establish effective management strategy, which will increase water access to the community.